2019
DOI: 10.1103/physrevb.99.094425
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic theory of magnon-drag electron flow in ferromagnetic metals

Abstract: A temperature gradient applied to a ferromagnetic metal induces not only independent flows of electrons and magnons but also drag currents because of their mutual interaction. In this paper, we present a microscopic study of the electron flow induced by the drag due to magnons. The analysis is based on the s-d model, which describes conduction electrons and magnons coupled via the s-d exchange interaction. Magnetic impurities are introduced in the electron subsystem as a source of spin relaxation. The obtained… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…This gives rise to a magnon spin-current [39]. Likewise, a ferromagnetic metal with a temperature gradient will host flow of both electrons and magnons coupled together through drag effects [40][41][42][43]. Coupling of flow of electrons and magnons has also been investigated in noncollinear antiferromagnetic metals [44].…”
Section: Introductionmentioning
confidence: 99%
“…This gives rise to a magnon spin-current [39]. Likewise, a ferromagnetic metal with a temperature gradient will host flow of both electrons and magnons coupled together through drag effects [40][41][42][43]. Coupling of flow of electrons and magnons has also been investigated in noncollinear antiferromagnetic metals [44].…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of the magnon drag to the Seebeck effect has been studied experimentally [15][16][17][18] and theoretically [19][20][21][22][23] from the 1960s. However, it appears that the magnon drag, related with an impurity band such as for the present alloy, is not sufficiently understood.…”
mentioning
confidence: 99%
“…Model Hamiltonian and Formulation of Electric and Thermal transports.-To study the magnon drag based on the electronic state shown in Fig. 1(c), we use a following model Hamiltonian [14,[21][22][23].…”
mentioning
confidence: 99%
See 2 more Smart Citations